Two-phased Mass Rarity and Extinction in Land Plants During the End-Triassic Climate Crisis - Lindström, Sofie (Frontiers in Earth Science, 2021)
Greenhouse gas emissions from large-scale volcanism in the Central Atlantic Magmatic Province is considered to have caused the end-Triassic mass extinction (201.5 million years ago), but the impact on land plants has been debated. Here, abundance changes in spores and pollen record the devastating effects this volcanic induced climate crisis had on coastal and near-coastal lowland mire vegetation around the European epicontinental sea and the European Tethys margin. Combined stress from rising air temperatures and changing climate at the onset of the crisis was exacerbated by a rapidly rising sea-level resulting in fragmentation and destruction of coastal and near-coastal lowland mire habitats, causing mass rarity and extinctions primarily in gymnosperm trees and shrubs adapted to these environments. The devastation of these habitats was further amplified by a subsequent sea-level fall leaving pioneering opportunists and herbaceous survivors to colonize disturbed areas in an environment stressed by increased wildfire activity and enhanced soil erosion. The pioneering flora was severely decimated in a second mass rarity phase and ultimately extirpated. The second mass rarity phase occurred just prior to and at the onset of a prominent negative excursion in δ13Corg. A subsequent sea-level rise appears to have restored some of the near-coastal mire habitats allowing some of plants to recover. The supraregional mass rarity during the end-Triassic crisis affected both previously dominant as well as rare plants and this resonates with ongoing and future climate change and attests to the vulnerability of coastal and lowland vegetation, especially rare plant species, to climatic and environmental disturbances, where rising sea-level threatens entire ecosystems.